The altitudinal patterns of global human gut microbial diversity - Lu-Lu Peng; Fu-Liang Qi; Kun Tan; Wen Xiao (BMC Microbiology)
Abstract Background The human gut microbiota is closely associated with human health, influencing not only overall well-being but also the incidence and treatment outcomes of diseases. Altitudinal gradients are considered to impact gut microbial community characteristics through factors such as environmental temperature, humidity, and lifestyle. While previous studies have reported altitudinal variations in human gut microbiota in specific regions, a comprehensive exploration of these patterns at a global scale is still lacking. In this study, we analyzed 16S rRNA amplicon sequencing data from healthy human gut microbiota, spanning altitudes from 3 m to 3850 m, obtained from multiple open-access databases. The analysis focused on elucidating the altitudinal patterns of microbial diversity, community composition, and functional profiles. Results After screening, a total of 6702 sequences from 15 countries were obtained. The diversity of human gut microbiota decreased with increasing altitude (R = -0.047, P < 0.001), but no consistent results were acquired among continents. The relative abundances of the genera Faecalibacterium and Blautia decreased with rising altitude (R = -0.131 and R = -0.135, respectively, P < 0.001 for both), while the relative abundance of the genus Prevotella increased with altitude (R = 0.336, P < 0.001). However, taxa such as Bacilliota, Bacteroides, and Bifidobacterium exhibit no consistent trends across different continents. The abundance of genes associated with the metabolism of terpenoids and polyketides, lipid metabolism, neurodegenerative diseases, and aging increased with altitude (R = 0.146, 0.037, 0.366, and 0.317, respectively; lipid metabolism P = 0.003, others P < 0.001). Conversely, the abundance of genes related to the immune system and carbohydrate metabolism decreased with increasing altitude (R = -0.166 and R = -0.219, respectively; P < 0.001 for both). Conclusion Altitude significantly influences diversity, composition, and functional attributes of the human gut microbiota.